Early Maps Of Dakota: Their Use In Placename Research - Thomas J. Gasque; John Van Balen (Names, 1989)
Abstract We have examined a number of historical maps of Dakota Territory from 1703 to 1889 for the purpose of making an index to placenames in this early period. These maps and the written documentation that often accompanies them have helped us resolve several troublesome onomastic questions.